MALDI-TOF mass spectrometry in the clinical mycology laboratory: identification of fungi and beyond. (April 2013) - Posteraro, Brunella; De Carolis, Elena; Vella, Antonietta; Sanguinetti, Maurizio
MALDI-TOF mass spectrometry (MS) is becoming essential in most clinical microbiology laboratories throughout the world. Its successful use is mainly attributable to the low operational costs, the universality and flexibility of detection, as well as the specificity and speed of analysis. Based on characteristic protein spectra obtained from intact cells – by means of simple, rapid and reproducible preanalytical and analytical protocols – MALDI-TOF MS allows a highly discriminatory identification of yeasts and filamentous fungi starting from colonies. Whenever used early, direct identification of yeasts from positive blood cultures has the potential to greatly shorten turnaround times and to improve laboratory diagnosis of fungemia. More recently, but still at an infancy stage, MALDI-TOF MS is used to perform strain typing and to determine antifungal drug susceptibility. In this article, the authors discuss how the MALDI-TOF MS technology is destined to become a powerful tool for routine mycological diagnostics.